The Role Of Adat Community As The Part Of Normative Systems In Paser - Melisa Safitri (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This paper examines the rights discourses and law as an arena of struggle in which local people attempt to gain and secure access to localities of value. To support these claims, multiple sources of legitimation were used. An access to land registration, which is the official responsibility of the National Land Agency (Badan Pertanahan Nasional, hereafter NLA). Nonetheless other official institutions such as the Department of Forestry and regional governments have authority over issues pertaining to land usage as well. Moreover, local custom (usually called adat can be a normative source opposing NLA decisions. This case study is concerned with the role of the NLA in deciding and maintaining land tenure at the district level, amidst the various interests of the district’s economy and the population. The research focuses on the ways in which the local population seeks redress of (perceived) grievances related to land issues: how do poor inhabitants of East Kalimantan deal with disputes over land? It shows how possibilities for addressing land related grievances have improved since Reformasi. First important change has been that local population groups have come o demand recognition of adat-based rights to land or compensation for adat lands in use by others. In many instances NGOs took the lead in this, organizing blockades and occupations. A second important change has been that elected government officials are nowadays given to considering the political benefits which they could gain from supporting these land claims. Rather than reverting to police or military assistance as was common in the New Order era, Paser’s government engages in dialogue and takes a diplomatic approach to settling these issues.